HUBUNGAN ASUPAN ENERGI DAN ASUPAN AIR PUTIH DENGAN PERSEN LEMAK TUBUH PADA REMAJA DI SMK HIDAYAH SEMARANG - Riagustin, Ovyka; Purbowati; Pontang , Galeh Septiar (JURNAL GIZI DAN KESEHATAN, 2019)
Background: Percentage of body fat is an indicator of nutritional status in anthropometric nutrition. The overweight prevalence of adolescents is increasing every year. High energy of stored the body as energy reserves in the form of glycogen as short-term energy reserves and in the form of fat as long-term reserves. Water consumption can be associated with a decrease in body fat percentage. Objective: To determine the correlation of water intake and energy intake with percentage of body fat in adolescents in vocational school Hidayah Semarang. Methods: This type of research is a correlation study using cross sectional approach with student population of SMK Hidayah Semarang. The sample of 85 respondents was taken using proportional random sampling method. The energy intake and the respondents' water intake were measured using semi-quantitative FFQ. Percentage of body fat of respondents were measured using BIA (Bioelectrical Impedance Analysis). Bivariate analysis used pearson test (Î± = 0.0001). Result: The highest category of energy sufficiency level was in the normal and mild deficit categories as many as 27 students (31.8%) and the smallest percentage with heavy deficit category was 2 students (2.4%). The highest categoryof water intake with enough categories is 56 students (64.7%) and the smallest percentage with less categories is 30 students (35.3%). The highest percentage of body fat category with normal category was 39 students (45.9%) and the smallest percentage with unnecessary category was 0 students (0%).There is a significant relationship between energy intake and water intake with percent body fat (p = 0.0001, p = 0.0001) Conclusion: There is a correlation between energy and water intake with body fat percentage Abstrak : Latar Belakang :Persen lemak tubuh sebagai indikator status gizi. Prevalensi gizi lebih pada remaja cenderung meningkat setiap tahunnya. Kelebihan energi disimpan tubuh sebagai cadangan energi dalam bentuk glikogen sebagai cadangan energi jangka pendek dan dalam bentuk lemak sebagai cadangan jangka panjang. Konsumsi air putih dapat dikaitkan dengan penurunan persen lemak tubuh Tujuan : Untuk mengetahui hubungan asupan air putih dan asupan energi dengan persen lemak tubuh pada remaja di SMK Hidayah Semarang. Metode : Jenis penelitian ini merupakan studi korelasi menggunakan pendekatan cross sectional dengan populasi siswa SMK Hidayah Semarang. Sampel sebanyak 85 responden diambil menggunakan metode proporsional random sampling. Asupan energi dan asupan air putih responden diukur menggunakan FFQ semi kuantitatif. Persen lemak tubuh responden diukur menggunakan BIA (Bioelectricallmpedance Analysis). Analisis bivariat menggunakan uji pearson (Î±=0,0001). Hasil : Kategori tingkat kecukupan energi terbanyak dengan kategori normal dan defisit ringan sebanyak 27 siswa (31,8%) dan persentase terkecil dengan kategori defisit berat sebanyak 2 siswa (2,4%). Kategori asupan air putih terbanyak dengan kategori cukup sebanyak 56 siswa (64,7%) dan persentase terkecil dengan kategori kurang sebanyak 30 siswa (35,3%). Kategori persen lemak tubuh terbanyak dengan kategori normal sebanyak 39 siswa (45,9%) dan persentase terkecil dengan kategori unnderfat sebanyak 0 siswa (0%). Terdapat hubungan yang bermakna antara asupan energi dan asupan air putih dengan persen lemak tubuh (p=0,0001, p=0,0001) Simpulan : Terdapat hubungan antara asupan energi dan asupan air putih dengan persen lemak tubuh.